Domestic Violence: Implication for Health Practitioners - Zabidah, Putit (UKM, 2011)
Domestic violence shattered the credibility of a home as safe haven. Feel oppressed, in fear, worried, uncertain, depressed, disturbed sleep, fragile, vulnerable, lost esteem and confidence, immobilized and paralysed, and lost direction in life were among the survivors' testimonies in my recent doctoral study on domestic violence. In each case it was just not merely a one off home scenario, but one that is ongoing and left the survivors ongoingly wounded and in grief. Yet these are kept silence in most instances, as domestic violence is considered as private and personal affair. What are the victims [survivors] barriers to reporting abuse and seeking help? Is that about the victim's internal fear and insecurity? Or it suggests that various external factors reinforce the victims to keep silence? If domestic violence is a public issue, what have the communities done to tackle the problem? What are the health team's barriers to enquire regarding abuse at the clinical level? How effective was our strategies? Have we been of help or have we added the 'salt to the wound'? What should also be stressed is the community awareness and active participation in curbing domestic violence. Ending gender discrimination and all forms of violence requires an understanding of the prevailing culture of bias and violence. In re emphasising the effective strategies, obligations and personnel responsibilities, this paper call for a continuity of public cooperation and support from the wider society. There need to be greater emphasis in multi-agency network and teamwork.